INTERRELATED ASPECTS OF LANGUAGE AND CULTURE (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2024)
Language and culture are deeply intertwined aspects of human society, influencing each other in countless ways. This paper explores the complex relationship between language and culture, examining how language shapes cultural practices and beliefs, and how culture in turn influences the development and use of language. Through a review of current research and case studies, this article highlights the interconnected nature of language and culture, and the importance of understanding this relationship for effective communication and intercultural understanding.